GLUT-1 may predict metastases and death in patients with locally advanced rectal cancer - Kim, Tae Hyun; Kwak, Yoonjin; Song, Changhoon; Lee, Hye Seung; Kim, Duck-Woo; Oh, Heung-Kwon; Kim, Jin Won; Lee, Keun-Wook; Kang, Sung-Bum; Kim, Jae-Sung (Frontiers in Oncology, 2023)
Glucose transporter-1 (GLUT-1) has been studied as a possible predictor for survival outcomes in locally advanced rectal cancer (LARC). We aimed to investigate the prognostic role of GLUT-1 in LARC using the data of 208 patients with clinical T3–4 stage and/or node-positive rectal adenocarcinoma, all of whom underwent neoadjuvant chemoradiotherapy (CRT) and subsequent total mesorectal excision (TME). Both pre-CRT and post-CRT specimens were immunohistologically stained for GLUT-1. Patients were classified into GLUT-1-positive and GLUT-1-negative groups and distant metastasis-free survival (DMFS) and overall survival (OS) was analyzed and compared. At a median follow-up of 74 months, post-CRT GLUT-1 status showed a significant correlation with worse DMFS (p=0.027, HR 2.26) and OS (p=0.030, HR 2.30). When patients were classified into 4 groups according to yp stage II/III status and post-CRT GLUT-1 positivity (yp stage II & GLUT-1 (-), yp stage II & GLUT-1 (+), yp stage III & GLUT-1 (-), yp stage III & GLUT-1 (+)), the 5-year DMFS rates were 92.3%, 63.9%, 65.4%, and 46.5%, respectively (p=0.013). GLUT-1 (-) groups showed markedly better outcomes for both yp stage II and III patients compared to GLUT-1 (+) groups. A similar tendency was observed for OS. In conclusion, post-CRT GLUT-1 may serve as a prognostic marker in LARC.